2001
DOI: 10.1002/1521-4141(200107)31:7<2179::aid-immu2179>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastogenesis is enhanced by activated B cells but suppressed by activated CD8+ T cells

Abstract: Host immune response is known to contribute to the progression of periodontitis, and alveolar bone destruction in periodontitis is associated with enhanced osteoclast activity. Therefore, we evaluated the roles of activated lymphocyte subsets in osteoclastogenesis. Osteoclast precursors were co‐cultured with activated lymphocytes (B, CD4+ T, CD8+ T) in the presence of either macrophage colony‐stimulating factor (M‐CSF) alone or M‐CSF plus soluble receptor activator of NF‐κB ligand (sRANKL), and subsequent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 38 publications
4
89
1
1
Order By: Relevance
“…For example, vitamin D3 stimulation of osteoclasts in vitro is enhanced by T-cell depletion (30); removing T cells would also remove any OX40 expressed by them. CD8 + T cells are also antiosteoclastogenic (15,31) and express high levels of OX40 during infections (32-34) associated with arthritic disease flare (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vitamin D3 stimulation of osteoclasts in vitro is enhanced by T-cell depletion (30); removing T cells would also remove any OX40 expressed by them. CD8 + T cells are also antiosteoclastogenic (15,31) and express high levels of OX40 during infections (32-34) associated with arthritic disease flare (35).…”
Section: Resultsmentioning
confidence: 99%
“…In the steady state, members of the TNF/TNF receptor superfamily play pivotal roles in multiple processes from lymphoid architecture to T-cell survival and bone homeostasis. RANK-L is a TNF family member produced by activated T cells (10,11), osteoblasts (12,13), keratinocytes (14), and B lymphocytes (15,16), among other cell types (reviewed in ref. 17), and, with macrophage colony-stimulating factor (M-CSF), drives osteoclast commitment from bone marrow precursors (18,19), leading to bone resorption.…”
mentioning
confidence: 99%
“…In vitro studies have demonstrated that B cells at several stages of differentiation, from early precursors to plasma cells, can support osteoclast formation (16,(35)(36)(37)(38)(39). Nonetheless, Weitzmann and colleagues have shown that ovariectomy led to similar amounts of bone loss in mice lacking mature B cells compared with control littermates, suggesting that mature B cells are not required for the bone loss caused by estrogen deficiency (40).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the presence of advanced periodontal lesions has been ascribed to an infiltration of B lymphocytes in the gingiva of patients with periodontitis. These activated B cells induce osteoclast differentiation (5).…”
mentioning
confidence: 99%